Assessing the Suitability of the Multilevel Governance Framework of the Laurentian Great Lakes Basin to Sustain the Quantity of its Stored Groundwater Resources - Weekes, Khafi (My University, 2021)
Water use in the Laurentian Great Lakes Basin (GLB) has long been governed by a framework of binational agreements between the United States and Canada, policies and decision-making standards of multilevel governments, and court rulings. Though groundwater quantity is not comprehensively monitored and groundwater insecurity is not widely reported throughout the Basin, in the context of rising regional populations increasing groundwater demand in high-use hotspots and climate change impacts simultaneously reducing aquifer recharge, this dissertation proactively examines the multi-scale interactions between multilevel governance and groundwater resources that can reduce sub-watershed scale groundwater storage (GWS) in high use and/or drought prone locales. Grounded on sustainable aquifer yield, adaptive governance and subsidiarity theories, and considered within the social-ecological system framework, the dissertation assesses the suitability of the governance framework to sustain GWS in high-groundwater-stress local contexts and provides governance reform recommendations. Chapter 1 provides the theoretical background and analytical framing necessary to contextualize the three original manuscripts of the dissertation that are presented in Chapters 2, 3 and 4. Chapter 2 highlights multilevel governance gaps undermining groundwater security in vulnerable situations. Chapter 3 collates reported cases of sub-watershed scale GWS vulnerabilities and conducts retrospective analysis to trace the origins of present-day groundwater governance weaknesses in the GLB. Chapter 4 is a case study of the City of Guelph that applies statistical methods to confirm the causal relationship between governance and GWS. Given the City’s unique governance approach, which has allowed it to maintain groundwater availability despite being wholly groundwater dependent and in a drought-prone region, the findings demonstrate the potential effectiveness of governance approaches featuring subsidiarity and adaptiveness in addressing groundwater insecurity in similarly vulnerable communities. Chapter 5 concludes the research, summarizing the dissertation’s core contributions and recommending further research relevant to maintaining GWS. The dissertation closes with a meta-analysis of Chapters 2, 3 and 4 collating their main findings into a conceptual whole to propose a novel framework of good governance principles to better sustain GWS in the Basin’s high-stress locales.
Keywords: Groundwater; Transboundary Water Policy